Manajemen Pembelajaran Paud Anak Sholeh Aswaja Rejang Lebong - Yanto, Murni (Insititut Agama Islam Negeri (IAIN) Curup, 2023)
The purpose of this study was to find out how the management of early childhood learning for pious children Aswaja Rejang Lebong, this study used a qualitative approach with descriptive analysis methods, collecting data through interviews, observation and documentation techniques. Research results: the teacher explains the RPPM, arranges research findings into opening, core and closing activities in RPPH, and prepares materials. Coordinating assignments, summarizing children according to age, educators distributing learning materials. Opening activities such as prayer and gross motor activities such as Dhuha prayer, core activities according to the RPPH, and closing activities such as material conversations that are less varied are better managed positively.